CHOICE FEEDING AND AMINO ACID REQUIREMENTS FOR BROILERS - Indarsih, B.; Pym, R.A.E. (Diponegoro University, 2011)
The study was conducted as a completely randomized design, with a factorial arrangement todetermine the response of commercial broilers to choice feeding and limiting amino acids on growth andcarcass performance. A total of 432 male birds were weighed at one-d-old and randomly distributed to48 wire-floored brooder cage each 1.0 m2. There were 2 sexes and 4 dietary treatments with 6 replicateseach of 9 birds. Birds were given one of three dietary regimens with dietary change every 7 days. Allgroups were fed free choice of summit and dilution diets. The estimated dietary level of crude protein atday-old was 240 g/kg and the level at 42 d was either 120, 150 or 180 g/kg for females or 130, 160 and190 g/kg for males. At 43 d of age, all birds from each dietary treatment were slaughtered formeasurement of body composition. Results reveal that lysine requirement for maximum gain in thisstudy was higher than NRC recommendation. The free choice-fed bird was significantly higher, in termsof growth and body composition than that obtained on the low dietary protein regimen.